Problems encountered by public elementary school principals in Quezon City in the implementation of the work-oriented curriculum - Thonghem, Poonsri 1943-
The respondents were 80 head teachers, assistant principals and principals in all the 70 public elementary schools in the Division of Quezon City. The problems encountered are (1) inability to interpret properly the objectives of work-oriented curriculum, (2) insufficient literature about the philosophy of the work-oriented curriculum, (3) insufficient knowledge of instructional objectives that develop work-oriented attitudes, and (4) inadequate background on the work-oriented curriculum.